GAMBARAN PERILAKU MEROKOK GURU DI LINGKUNGAN SEKOLAH MENENGAH PERTAMA DI PEKANBARU - Sari, Suci Maya; Afandi, Dedi; Fauzi, Zarfiardy Aksa (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTSmoking remains one of the leading problem that can't be resolved until now. One of the important factor is the junior high school as education institutions that produce the next generations that not only excellent in achievment but also care about health of themselves and environment. Teachers as role models in schools also had important role in students attitude and behavior formation. This research aims to determined the smoking behavior among teachers in junior high school in Pekanbaru. This research was a descriptive study with cross-sectional approach. This study had been done on September 2014 with 210 teachers from seven Junior High Schools in Pekanbaru as respondents. Results showed that all respondents (100%) had good knowledge, good attitude as much as 202 respondents (96.2%), and as many as 187 people (89%) had good behavior. Keywords : smoking , knowledge , attitudes and behavior